Becoming of practice and internship as students research activity forms. - Kuznetsova V.N (Kharkov National Pedagogical University, 2010)
In the article the author considered the becoming of practice and internship as students research activity forms at Ukrainian higher professional educational establishments at the end of ХІХ - at the beginning of ХХ century. The educational practice programs (in educational establishment workshops), production practice programs (on the basis of enterprises) and pregraduation internship are analysed. The special feature of in-service trade education for students was the practice in the process of labour activity at the enterprises. The students studying of professional activity influence on personal qualities and the way of life was obligatory during internship.